Rice endosperm is cost-effective for the production of recombinant griffithsin with potent activity against HIV - Vamvaka,E; Arcalis,E; Ramessar,K; Evans,A; O'Keefe,BR; Shattock,RJ; Medina,V; Stöger,E; Christou,P; Capell,T (Plant Biotechnology Journal, 2016)
Protein microbicides containing neutralizing antibodies and antiviral lectins may help to reduce the rate of infection with human immunodeficiency virus (HIV) if it is possible to manufacture the components in large quantities at a cost affordable in HIV-endemic regions such as sub-Saharan Africa. We expressed the antiviral lectin griffithsin (GRFT), which shows potent neutralizing activity against HIV, in the endosperm of transgenic rice plants (Oryza sativa), to determine whether rice can be used to produce inexpensive GRFT as a microbicide ingredient. The yield of OSGRFT in the best-performing plants was 223 μg/g dry seed weight. We also established a one-step purification protocol, achieving a recovery of 74% and a purity of 80%, which potentially could be developed into a larger-scale process to facilitate inexpensive downstream processing. OSGRFT bound to HIV glycans with similar efficiency to GRFT produced in Escherichia coli. Whole-cell assays using purified OSGRFT and infectivity assays using crude extracts of transgenic rice endosperm confirmed that both crude and pure OSGRFT showed potent activity against HIV and the crude extracts were not toxic towards human cell lines, suggesting they could be administered as a microbicide with only minimal processing. A freedom-to-operate analysis confirmed that GRFT produced in rice is suitable for commercial development, and an economic evaluation suggested that 1.8 kg/ha of pure GRFT could be produced from rice seeds. Our data therefore indicate that rice could be developed as an inexpensive production platform for GRFT as a microbicide component.